Development of HOTS Assessment Instruments on Static Electricity Materials for High School Level - Athari Hany Milia; Silvi Trisna; Iing Rika Yanti (Universitas Lambung Mangkurat, 2022)
This development research is motivated by the lack of Higher Order Thinking Skill (HOTS) assessment instruments at 3 Public High School in physics subjects, especially static electricity. One of the efforts to assist teachers in knowing the development of students' higher-order thinking skills is by developing the HOTS assessment instrument. This study aims to develop a valid and practical HOTS assessment instrument for class XII static electricity at SMA N 3 Padang and to analyze the reliability of the items using the 4-D model research and development (R&D) method (four-D models) developed by Thiagarajan. , consists of 4 stages: (1) define, (2) design, (3) develop, and (4) disseminate. However, this research is limited to the development stage due to time and cost constraints. The research results on needs analysis show that the static electricity material developed follows the 2013 curriculum seen from Basic Competencies, along with its indicators. Validation analysis with three validators obtained 88.32% results with very valid category; practicality analysis obtained 95.55% results with very practical category; and reliability analysis the question obtained is 0.24, which is categorized as low. The implications of this research are to assist teachers in developing HOTS assessment instruments on other materials.